SAT0038 Factors Predicting Pain and Early Discontinuation of Tumour Necrosis Factor-Alpha-Inhibitors in People with Rheumatoid Arthritis: Results from the British Society for Rheumatology BIOLOGICS Register. (10th June 2014) - Mcwilliams, D.F.; Walsh, D.A.
Abstract : Background: Pain is a major problem in RA, but is not fully explained by inflammation. Objectives: We investigated factors predicting bodily pain 1 year after initiation of anti-TNF or conventional DMARD therapy change in British Society for Rheumatology Biologics Register (BSRBR) participants with RA, and baseline patient-reported factors that predicted discontinuation of TNFα-inhibitors. Methods: Data were retrieved from BSRBR-RA databases for baseline and up to 1 year after commencing TNFα-inhibitors (n=11995) or non-biologic DMARDs (n=3632). Norm-based SF36-Bodily Pain scores were used. DAS28-P was derived as the proportion of 28 joint disease activity score attributed to patient-reported factors. Adjusted odds ratios (aOR) using logistic regressions were calculated. Results: Pain was severe at baseline (medians 25, 30) and incompletely improved during follow up (medians 34, 34 respectively) in TNF-inhibitor and control cohorts. Baseline pain was associated with DAS28-P, worse function, worse mental health, and higher DAS28. After logistic regression, independent significant predictors of worse than median pain at follow up after commencing either TNF-inhibitor or non-biologic DMARD were baseline pain, DAS28-P, worse function, worse mental health and co-morbidities. Older age, male gender, smoking and high BMI were additional predictors of worse pain outcomes in participants who received TNFα-inhibitors (Table 1 ). Some DMARDs were associated with better pain. Baseline pain predicted discontinuation of TNFα-inhibitors within the first year (aOR 1.13 (95% CI 1.05–1.22)); as did smoking (1.20 (1.06–1.36)), worse function (1.17 (1.08–1.26)), and systemic manifestations (1.15 (1.02–1.28)). Conclusions: Pain may improve but remains a problem for people with treated RA. Worse pain outcomes are predicted by factors different to those typically used to predict inflammatory disease activity. Pain predicts treatment failure with TNFα-inhibitors. Improved pain management should complement inflammatory disease suppression in RA. Acknowledgements: Funding: Pfizer Ltd. We would like to acknowledge the BSR Biologics Register for the collection, provision and preparation of the data used for this study. Disclosure of Interest: D. Mcwilliams Grant/research support: Pfizer Ltd, D. Walsh Grant/research support: Pfizer Ltd DOI: 10.1136/annrheumdis-2014-eular.1549